2010
DOI: 10.1016/j.socscimed.2010.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Can we explain increases in young people’s psychological distress over time?

Abstract: This paper aims to explain previously described increases in self-reported psychological distress between 1987 and 2006 among samples identical in respect of age (15 years), school year and geographical location (West of Scotland). Such increases might be explained by changes in exposure (changes in levels of risk or protective factors) and/or by changes in vulnerability (changes in the relationship between risk/protective factors and psychological distress). Key areas of social change over this time period al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
97
1
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 63 publications
4
97
1
14
Order By: Relevance
“…Specifically, the rising number of children raised by one parent alone may be related to increases in psychosocial problems. However, two British studies did not find evidence for an association between the lower number of adolescents living with both biological parents and the higher rate of emotional problems and psychological distress seen between the 1980s and 2006 (Collishaw et al, 2010;Sweeting et al, 2010). On the other hand, time trends in other family variables, such as a growing number of reported arguments with parents and increased maternal stress, were associated with greater psychological distress in the UK from the 1980s through 2006 (Schepman et al, 2011;Sweeting et al, 2010).…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Specifically, the rising number of children raised by one parent alone may be related to increases in psychosocial problems. However, two British studies did not find evidence for an association between the lower number of adolescents living with both biological parents and the higher rate of emotional problems and psychological distress seen between the 1980s and 2006 (Collishaw et al, 2010;Sweeting et al, 2010). On the other hand, time trends in other family variables, such as a growing number of reported arguments with parents and increased maternal stress, were associated with greater psychological distress in the UK from the 1980s through 2006 (Schepman et al, 2011;Sweeting et al, 2010).…”
mentioning
confidence: 91%
“…However, in one British study, a series of indicators of family economy were not found to be related to time trends in psychological distress Secular trends in depressive symptoms 5 among adolescents (Sweeting et al, 2010). Finally, changes in adolescents' lifestyle, self-concept and values have been put forward as potential explanatory factors (Rutter & Smith, 1995;Sweeting et al, 2010). Thus far, one study has examined several such factors, including changes in religious behavior, youth culture, computer gaming, obesity, and worries about weight and looks (Sweeting et al, 2010).…”
mentioning
confidence: 96%
See 3 more Smart Citations